Relação entre postura, queixa dolorosa e lesão em bailarinas clássicas - Couto, Amanda Gomes de Assis; Pedroni, Cristiane Rodrigues [UNESP] (My University, 2013)
Introduction: Due to the high recurrence of pain complaints and the increasing incidence of musculoskeletal injuries and postural changes in dance practice, researches related to this issue gained greater importance in scientific community. Objective: This study aimed to evaluate complaints and pain threshold, postural misalignments and the incidence of injuries in dancers noting if there is a relationship between these variables. Method: Participants were 15 ballet dancers in Marília - SP. We used photogrammetry for postural analysis, the McGill Pain Questionnaire for pain location of the volunteer, algometry pressure for measuring the threshold of pain perception and Referred Morbidity to verify and characterize the incidence of injuries this population. In the data analysis we use to percentage to quantify the data from questionnaires and Pearson correlation test angles of photogrammetry correlating with the values of the threshold of pain perception. Results: 73.33% of dancers reported to have suffered some kind of injury in the last year. The area of greatest pain complaint checked at McGill, was the region of the foot (73.30%). Conclusion: There was an agreement between regions of injury and pain, however, there wasn’t a correlation between the threshold of pain tolerance and postural angles.

Introdução: Devido à alta recorrência da queixa dolorosa e a crescente incidência de alterações posturais e lesões musculoesqueléticas na prática da dança, as pesquisas relacionadas a este assunto ganharam maior importância na comunidade científica. Objetivo: Avaliar a queixa e o limiar doloroso, os desalinhamentos posturais, a incidência de lesões em bailarinos e verificar se há uma relação entre essas variáveis. Método: Participaram da pesquisa 15 bailarinas clássicas da cidade de Marília – SP. Utilizou-se a fotogrametria para análise postural, o Questionário de Dor McGill para localização da dor do voluntário, algometria de pressão para mensuração do limiar de percepção dolorosa e o Inquérito de Morbidade Referida para verificar e caracterizar a incidência de lesões nessa população. Na análise dos dados utilizou-se a porcentagem para quantificar os dados dos questionários e o teste de correlação de Pearson correlacionando os ângulos da fotogrametria com os valores do limiar de percepção dolorosa. Resultados: 73,33% das bailarinas relatam ter sofrido algum tipo de lesão no último ano. A área de maior queixa dolorosa assinalada no McGill foi a região do pé (73,30%). Conclusão: Houve concordância entre regiões de lesão e dor, no entanto, não houve correlação entre os ângulos posturais e o limiar de percepção dolorosa.
Posture, pain and injury in ballet dancer
Keywords: postura; Dor; bailarinos